2015
DOI: 10.1039/c5nj00593k
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic amphiphilic nanocomposites based on silica–carbon for sulphur contaminant oxidation

Abstract: Magnetic amphiphilic nanocomposites based on silica–carbon promote the desulfurization of diesel fuel and their activity is enhanced by Mo nuclei supported on the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…The increased polarity and high interfacial area were also responsible for facilitating the extraction of DBTO 2 [143]. Figure 11 shows the presumed mechanism for emulsified systems, adapted from elsewhere [144][145][146]. Other authors have also reported ODS emulsion systems that rely upon amphiphilic catalysts to increase catalytic activity [147].…”
Section: Amphiphilic Carbonsmentioning
confidence: 97%
“…The increased polarity and high interfacial area were also responsible for facilitating the extraction of DBTO 2 [143]. Figure 11 shows the presumed mechanism for emulsified systems, adapted from elsewhere [144][145][146]. Other authors have also reported ODS emulsion systems that rely upon amphiphilic catalysts to increase catalytic activity [147].…”
Section: Amphiphilic Carbonsmentioning
confidence: 97%
“…Teixeira et al [37] produziram nanotubos de carbono sobre Al 2 O 3 contendo Fe/Mo e aplicaram-nos num meio bifásico com H 2 O 2 para remover DBT e QN de uma fase oleosa, tendo sido observada a sua completa oxidação em 200 e 30 min de reação, respetivamente. Oliveira et al [41] usaram compósitos de SiC na oxidação bifásica de compostos sulfurados numa amostra de diesel, permitindo uma remoção de 57% desses compostos. Santos et al [38] testaram compósitos de nanotubos de carbono/nanotubos de titânio para a oxidação em meio bifásico do amarelo de metilo (MY) e do álcool benzílico com H 2 O 2 , atingindo 100% de remoção de 30 mg L -1 de MY em 60 min de reação e mais de 90% de álcool benzílico em 3 h de reação.…”
Section: Processos Avançados De Oxidação (Aops)unclassified